Exploratory Analysis on Overall Survival after Either Surgery or Stereotactic Radiotherapy for Lung Oligometastases from Colorectal Cancer. Issue 8 (August 2016) - Filippi, A.R.; Guerrera, F.; Badellino, S.; Ceccarelli, M.; Castiglione, A.; Guarneri, A.; Spadi, R.; Racca, P.; Ciccone, G.; Ricardi, U.; Ruffini, E.
Abstract: Aims: Lung metastasectomy and, more recently, stereotactic body radiotherapy (SBRT), are frequently proposed to stage IV oligometastatic colorectal cancer (CRC) patients. In the absence of a randomised comparison between the two treatments, we aimed to retrospectively explore the effect on overall survival and progression-free survival (PFS) in a comparative cohort study. Materials and methods: We included patients who consecutively underwent surgery ( n = 142) or SBRT ( n = 28) as first local therapy at the time of lung progression, between 2005 and 2012. Both overall survival and PFS functions according to treatment were calculated using the Kaplan–Meier method and compared using the Log-rank test. The effect of treatment on overall survival and PFS was estimated by Cox models using different adjustment methods. Results: Patients receiving SBRT were older and were treated more recently, whereas the two cohorts were similar for most baseline prognostic factors. Overall survival at 1 and 2 years was 0.89 and 0.77 for SBRT and 0.96 and 0.82 for surgery ( P = 0.134), respectively. Multivariable analyses did not highlight a clear treatment effect on overall survival (adjusted hazard ratioSBRT versus surgery = 1.71; 95% confidence interval 0.82–3.54; P = 0.149) and even smaller differences using the inverse probability treatment weighting method (hazard ratioSBRT versus surgery = 1.28, 95% confidence interval 0.58–2.82; P = 0.547). The results of PFS were unreliable because different follow-up protocols were applied in the two cohorts. Conclusion: With limitations consisting in the retrospective observational design and different sample sizes, the results of this explorative analysis indicate that overall survival probability after SBRT is similar to surgery for the first 2 years from treatment. This finding supports the need for high-quality trials comparing different treatment modalities for lung oligometastases from CRC. Highlights: The study was retrospective, comparing two treatments for CRC lung oligometastases. Results showed promising survival rates after stereotactic radiotherapy. Overall survival at 2 years seems to be similar between surgery and radiotherapy. Limits are a smaller sample and a shorter follow-up for the radiotherapy cohort. Stereotactic radiotherapy should be included in prospective trials.